Design of Steel Structures, 2e. - Ram, K. S. Sai. (2013)
This book on Design of Steel Structures uses the Limit State method and follows the latest BIS Code, BIS: 800: 2007.With a perfect mix of theory with relevant applications, the book spells out the most recent design methodologies to make it an excellent offering to students and practising engineers.
Appendix G : Properties of Cold-formed Light-gauge Sections -- References -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books